Noise levels in a neonatal intensive care unit in the Cape Metropole - Nathan, Lisa (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMedSc (Interdisciplinary Health Sciences. Speech-Language and Hearing Therapy))--University of Stellenbosch, 2007.